The Role of National Values in The Formation of Cultural Code In Society - Doston Khamidov (Genius Journals, 2024)
Thе state of Uzbek national moral values in the conditions of the dictatorial Soviet regime, the worship of Stalin, the falsification of history, the formation of socialism as а single value are covered.
Keywords: Reconstruction; Universities of Rural Culture; culture code